The Cardiothoracic Surgeon - Arafat, Amr Ahmed; Hassouna, Ahmed; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
The Cardiothoracic Surgeon (CTS) is the official journal of the Egyptian Society of Cardiothoracic Surgery. It is a peer-reviewed, open access journal which publishes high-quality original scientific research documenting progress in cardiac and thoracic surgery. The journal publishes articles on a range of topics including clinical trials, outcomes and complications of experimental procedures, surgical operations and therapeutic approaches for high-risk patients with congenital and cardiothoracic diseases. It is an international journal which accepts submissions from countries across the world. It is aimed at cardiothoracic surgeons, cardiologists, chest physicians and allied health professionals.
Keywords: Public health; Heart$1 (BSurgery.s; Public Health; Cardiac Surgery